Effect of essential oils on the growth of Fusarium verticillioides and Fumonisin contamination in corn - Fandohan, P.; Gbenou, J.D.; Gnonlonfin, G.J.B.; Hell, K.; Marasas, W.F.O.; Wingfield, M.J. (American Chemical Society, 2004)
Essential oils extracted by hydrodistillation from local plants in Benin, western Africa, and oil from seeds of the neem tree (Azadirachta indica) were evaluated in vitro and in vivo for their efficacy against Fusarium verticillioides infection and fumonisin contamination. Fumonisin in corn was quantified using a fluorometer and the Vicam method. Oils from Cymbopogon citratus, Ocimum basilicum, and Ocimum gratissimum were the most effective in vitro, completely inhibiting the growth of F. verticillioides at lower concentrations over 21 days of incubation. These oils reduced the incidence of F. verticillioides in corn and totally inhibited fungal growth at concentrations of 8, 6.4, and 4.8 μL/g, respectively, over 21 days. At the concentration of 4.8 μL/g, these oils did not affect significantly fumonisin production. However, a marked reduction of fumonisin level was observed in corn stored in closed conditions. The oils adversely affected kernel germination at 4.8 μL/g and therefore cannot be recommended for controlling F. verticillioides on stored corn used as seeds, when used at this concentration. The oil of neem seeds showed no inhibitory effect but rather accelerated the growth of F. verticillioides.